1996
DOI: 10.1007/bf00019100
|View full text |Cite
|
Sign up to set email alerts
|

Higher-plant chloroplast and cytosolic fructose-1,6-bisphophosphatase isoenzymes: origins via duplication rather than prokaryote-eukaryote divergence

Abstract: Full-size cDNAs encoding the precursors of chloroplast fructose-1,6-bisphosphatase (FBP), sedoheptulose-1,7-bisphosphatase (SBP), and the small subunit of Rubisco (RbcS) from spinach were cloned. These cDNAs complete the set of homologous probes for all nuclear-encoded enzymes of the Calvin cycle from spinach (Spinacia oleracea L.). FBP enzymes not only of higher plants but also of non-photosynthetic eukaryotes are found to be unexpectedly similar to eubacterial homologues, suggesting a eubacterial origin of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 45 publications
4
33
0
Order By: Relevance
“…SBPase was previously described as an essential enzyme of green plants that was acquired after primary endosymbiosis (Martin et al 1996). In this study, we document the presence of SBPase in all lineages of photosynthetic eukaryotes containing primary plastids including green plants, rhodophytes, and glaucophytes (Plantae) as well as in all lineages with complex green (euglenophytes, chlorarachniophytes) or complex red plastids (haptophytes, cryptophytes, diatoms, dinoflagellates) (Fig.…”
Section: Origin Function and Distribution Of Sbp Genessupporting
confidence: 59%
See 3 more Smart Citations
“…SBPase was previously described as an essential enzyme of green plants that was acquired after primary endosymbiosis (Martin et al 1996). In this study, we document the presence of SBPase in all lineages of photosynthetic eukaryotes containing primary plastids including green plants, rhodophytes, and glaucophytes (Plantae) as well as in all lineages with complex green (euglenophytes, chlorarachniophytes) or complex red plastids (haptophytes, cryptophytes, diatoms, dinoflagellates) (Fig.…”
Section: Origin Function and Distribution Of Sbp Genessupporting
confidence: 59%
“…Several phylogenetic analyses of SBP and FBP sequences have shown that they are homologous and demonstrated the highly distinct nature of the monophyletic SBP subtree (Hannaert et al 2003;Martin et al 1996;Rogers and Keeling 2004). Figure 2 shows the maximum likelihood tree (PhyML) of 37 eukaryotic SBP sequences based on 197 aa positions.…”
Section: Phylogenetic Analyses Of Sbp Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…We have used genomic information to search for the presence of genes coding for potential glycosomal proteins as identified by the presence of so-called peroxisometargeting signals (PTSs), either at their C terminus (PTS1) or near their N terminus (PTS2). Most strikingly, we identified in T. brucei, a gene with a complete ORF for a homolog of SBPase, an enzyme typical of the Calvin cycle of photosynthetic organisms and has been thus far encountered only in the chloroplasts of green algae and plants (18). The inferred protein sequence has a PTS1 (-SKL) at its C terminus, suggestive of a glycosomal localization.…”
Section: Resultsmentioning
confidence: 98%